2014
DOI: 10.1105/tpc.114.129122
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Study ofKNOXRegulatory Network Reveals Brassinosteroid Catabolic Genes Important for Shoot Meristem Function in Rice  

Abstract: In flowering plants, knotted1-like homeobox (KNOX) transcription factors play crucial roles in establishment and maintenance of the shoot apical meristem (SAM), from which aerial organs such as leaves, stems, and flowers initiate. We report that a rice (Oryza sativa) KNOX gene Oryza sativa homeobox1 (OSH1) represses the brassinosteroid (BR) phytohormone pathway through activation of BR catabolism genes. Inducible overexpression of OSH1 caused BR insensitivity, whereas loss of function showed a BR-overproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 47 publications
7
131
0
Order By: Relevance
“…Plant tissue including 3-wk-old tiller buds as well as young ear primordia smaller than 5 mm were dissected from field grown B73 or tb1-r. About 1 g of tissue per biological replicate was then fixed in 1% formaldehyde. Nuclei extraction and chromatin immunoprecipitation using α-TB1 antibody were performed as described previously (56). Normal goat anti-Guinea pig IgG (sc-2711; Santa Cruz Biotechnology) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Plant tissue including 3-wk-old tiller buds as well as young ear primordia smaller than 5 mm were dissected from field grown B73 or tb1-r. About 1 g of tissue per biological replicate was then fixed in 1% formaldehyde. Nuclei extraction and chromatin immunoprecipitation using α-TB1 antibody were performed as described previously (56). Normal goat anti-Guinea pig IgG (sc-2711; Santa Cruz Biotechnology) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings indicate that the drl genes regulate a suite of traits in the leaf and stem similar to those affected by BR; however, a connection between these two important developmental regulators has not been established. drl1 mutant alleles together with drl2 natural variant and mutant alleles condition a phenotype that strongly resembles aspects of rice mutants that have elevated BR levels or enhanced BR signaling (Zhang et al, 2009;Tong et al, 2012;Tsuda et al, 2014;Sun et al, 2015): drl mutants have narrow leaves, increased leaf angle, expanded auricles, reduced sclerenchyma, and elongated internodes (Figures 1 to 3; Supplemental Figure 3). One peculiar phenotype observed in drl1-R; drl2-M plants was complete fusion along the sheath margins at some adult nodes Supplemental Figure 3I), a phenotype related to BR hypersensitivity in Arabidopsis (Bell et al, 2012;Gendron et al, 2012).…”
Section: Primordia-derived Activities Of Drl Genes Regulate Shoot Mermentioning
confidence: 99%
“…BRs influence leaf bending and internode elongation in maize (Hartwig et al, 2011;Makarevitch et al, 2012;Kir et al, 2015) and rice (Wada et al, 1981;Cao and Chen, 1993;Yamamuro et al, 2000;Hong et al, 2002;Zhang et al, 2009;Tong et al, 2012;Tsuda et al, 2014;Sun et al, 2015), regulate adaxial cell elongation in auricles (Wada et al, 1981;Cao and Chen, 1993), reduce abaxial sclerenchyma proliferation (Sun et al, 2015) in rice, and cause organ fusion in Arabidopsis (Bell et al, 2012;Gendron et al, 2012). Our findings indicate that the drl genes regulate a suite of traits in the leaf and stem similar to those affected by BR; however, a connection between these two important developmental regulators has not been established.…”
Section: Primordia-derived Activities Of Drl Genes Regulate Shoot Mermentioning
confidence: 99%
“…Early observations that the rice KNOX gene OSH1 increases cytokinin and decreases gibberellin levels in transgenic tobacco plants prompted Kusaba et al (1998) to hypothesize that OSH1 affects plant hormone metabolism. Subsequent studies showed that KNOX genes activate cytokinin biosynthesis (Yanai et al, 2005) and repress gibberellin production (Bolduc and Hake, 2009).In an effort to decipher KNOX regulatory networks in rice, Tsuda et al (2014) examined the effect of altering the expression of OSH1 using an inducible OSH1 overexpressor and a loss-of-function osh1 mutant. Whereas overexpression of OSH1 caused brassinosteroid (BR) insensitivity, resulting in plants with twisted, erect leaf blades and severely shortened leaf sheaths, OSH1 loss-of-function mutants resembled BR overproducers, exhibiting increased coleoptile growth, defects in boundary formation between the SAM and first leaf primordium, and an increased lamina joint angle of the second leaf.…”
mentioning
confidence: 99%
“…In an effort to decipher KNOX regulatory networks in rice, Tsuda et al (2014) examined the effect of altering the expression of OSH1 using an inducible OSH1 overexpressor and a loss-of-function osh1 mutant. Whereas overexpression of OSH1 caused brassinosteroid (BR) insensitivity, resulting in plants with twisted, erect leaf blades and severely shortened leaf sheaths, OSH1 loss-of-function mutants resembled BR overproducers, exhibiting increased coleoptile growth, defects in boundary formation between the SAM and first leaf primordium, and an increased lamina joint angle of the second leaf.…”
mentioning
confidence: 99%